STRATEGIC MANAGEMENT TECHNICAL SERVICE OF AUTOENTERPRISE ON THE BASIS OF KEY AIMS - Vladimir Trubitsyn (Вестник Северо-Кавказского федерального университета, 2022)
In the article for autoenterprises the algorithm of realization ofstrategic management is offered on the basis of key indexes of efficiency. Taken approach division of fulfiling the summary strategic plan and operative activity